Experiences of seeking and accessing medical care among persons with major depression: A qualitative descriptive study of persons with depression in China - Zhou, Yan Hua; Leung, Doris; Lin, Jian Kui; Hu, Li Chan; Lin, Xiao Yang; Zhang, Xuelin; Mak, Yim Wah (Frontiers in Psychiatry, 2023)
Introduction A large number of people in China are affected by depression, yet tend to delay seeking treatment. This study aims to explore persons living with depression and their journey of diagnoses and seeking professional medical help in China. Methods Semi-structured interviews were conducted with 20 persons who visiting physicians to be diagnosed and receive professional help from a large mental health center in Guangzhou, Guangdong province, China. Individual interviews were conducted and data were analyzed using content analysis. Results Three themes were identified from the findings: (1) “noticed something was wrong”; (2) negotiated decisions with their own narratives and the personal suggestions of others; and (3) gave new meaning to their experiences of depression, whereby they sought medical treatment. Discussion The findings of the study indicated that the impact of progressive depressive symptoms on the participants’ daily lives was a strong motivation for them to seek professional help. The obligation to care for and support their family prevented them from initially disclosing their depressive symptoms to family members, but eventually prompted them to seek professional help and persist in follow-up treatment. Some participants experienced unexpected benefits (e.g., relief at no longer feeling “alone”) during their first visit to the hospital for depression or when they were diagnosed with depression. The results suggest a need to continue to actively screen for depression and provide more public education to prevent negative assumptions and reduce public and personal stigmatization of those with mental health problems.